Irradiated mononuclear cells express significant in vitro cytotoxic activity: promise for in vivo clinical efficacy of irradiated mismatched donor lymphocytes infusion. (April 2014) - Tsirigotis, Panagiotis; Resnick, Igor B; Kapsimalli, Violetta; Dray, Liliane; Psarra, Ekaterini; Samuel, Simha; Spyridonidis, Alexander; Konsta, Evi; Vikentiou, Myrofora; Or, Reuven; Slavin, Shimon; Shapira, Michael Y
Background: Relapse of the original disease remains the most common cause of treatment failure after allogeneic hematopoietic stem cell transplantation (allo-SCT). Patients who relapse post-allo-SCT can achieve prolonged remission after donor lymphocyte infusion. Donor lymphocyte infusion as well as other immunotherapeutic strategies are usually complicated by severe graft versus host disease.Aim: In the present study, we examined the effect of irradiation on the cytotoxic activity of mononuclear cells (MNCs).Materials & methods: Cytotoxic activity of fresh and irradiated MNCs from healthy donors was tested against the leukemic cell line K562 and against fresh leukemic cells from patients with acute myeloid leukemia. Cytotoxicity was assessed by using a flow-cytometry assay.Results & discussion: Interestingly, we observed that 25 Gy irradiated MNCs retain significant cytotoxic activity against K562. Based on these in vitro data, the safety and efficacy of irradiated haploidentical, IL-2-activated lymphocytes were tested in six patients after allo-SCT. Acute skin graft versus host disease developed in two patients and was resolved after a short course of steroids. One patient with mixed chimera converted to full donor chimera after infusion of irradiated donor cells.Conclusion: The efficacy of irradiated haploidentical lymphocytes should be further tested in a larger number of patients.